Odpowiedź :
1.
a) a*p
b) x/5
c) x/2
2.
x³+x+1 dla x=2
2³+2+1=8+2+1=11
3.
-2 (4z+9) dla z=-3
-2(4*(-3)+9) = -2(-12+9)=-2*(-3)=6 Odpowiedz A
4.
a) ax*0,5x=0,5ax²
b) -x*(-5x) = 5x²
c) 22a*4a=88a²
5.
a) -2x-2x = -4x
b) 6m-(-2m) = 6m+2m = 8m
Odpowiedź:
Szczegółowe wyjaśnienie:
Zad 1
a) ap
b) x/5
c) x/2
Zad 2
x²+x+1 dla x = 2 = 2² + 2 + 1 = 7
Zad 3
-2(4z+9) dla z = -3 = -2 ( 4 razy (-3) +9) = -2 (-12+9) = -2 razy -3 = 6, odpowiedź A
Zad 4
a) "ax" razy 0,5x = (ax²)/ 2
b) -x (-5x) = 5x²
c) (22a razy 4a)= 88a²
Zad 5
-2x-2x= -4x
6m - (-2m) = 8m